1960
DOI: 10.1128/jb.79.6.841-848.1960
|View full text |Cite
|
Sign up to set email alerts
|

S-Adenosylmethionine in the Vacuole of Candida Utilis

Abstract: Recently, it has been demonstrated by ultraviolet microscopy that S-adenosylmethionine is accumulated in the vacuole of Candida utilis (Svihla and Schlenk, 1959). The exceptional 1 Research performed under the auspices of the U. S. Atomic Energy Commission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
26
0

Year Published

1964
1964
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(28 citation statements)
references
References 9 publications
2
26
0
Order By: Relevance
“…From this pool methyl groups are transferred by specific methyltransferases on to their physiological acceptors.Since the early experiments of Stekol et al (1958), who observed an increased formation of methylated products by rat liver slices in the presence of exogenous SAM, various groups have looked for a specific uptake system for SAM. This would offer the opportunity to label the internal SAM pool directly and allow measurements of transfer of methyl groups on to proteins without interference Abbreviations used: Hepes, 4-(2-hydroxyethyl)l-piperazine-ethanesulphonic acid; PtdEtn, phosphatidylmonoethanolamine; Ptd[EtnI2, phosphatidyldiethanolamine; PtdCho, phosphatidylcholine; SAM, S-adenosyl-L-methionine; SDS, sodium dodecyl sulphate.be incorporated into plasma-membrane with the incorporation of labelled methionine via protein synthesis.An uptake system for SAM has indeed been described for yeast cells by Svihla & Schlenk (1960) and by Spence (1971) and was characterized by Murphy & Spence (1972). The transport was temperature-and energy-dependent, had an apparent Km for SAM of 3.3,pM and was inhibited by S-adenosylhomocysteine and S-adenosylethionine.…”
mentioning
confidence: 90%
See 1 more Smart Citation
“…From this pool methyl groups are transferred by specific methyltransferases on to their physiological acceptors.Since the early experiments of Stekol et al (1958), who observed an increased formation of methylated products by rat liver slices in the presence of exogenous SAM, various groups have looked for a specific uptake system for SAM. This would offer the opportunity to label the internal SAM pool directly and allow measurements of transfer of methyl groups on to proteins without interference Abbreviations used: Hepes, 4-(2-hydroxyethyl)l-piperazine-ethanesulphonic acid; PtdEtn, phosphatidylmonoethanolamine; Ptd[EtnI2, phosphatidyldiethanolamine; PtdCho, phosphatidylcholine; SAM, S-adenosyl-L-methionine; SDS, sodium dodecyl sulphate.be incorporated into plasma-membrane with the incorporation of labelled methionine via protein synthesis.An uptake system for SAM has indeed been described for yeast cells by Svihla & Schlenk (1960) and by Spence (1971) and was characterized by Murphy & Spence (1972). The transport was temperature-and energy-dependent, had an apparent Km for SAM of 3.3,pM and was inhibited by S-adenosylhomocysteine and S-adenosylethionine.…”
mentioning
confidence: 90%
“…An uptake system for SAM has indeed been described for yeast cells by Svihla & Schlenk (1960) and by Spence (1971) and was characterized by Murphy & Spence (1972). The transport was temperature-and energy-dependent, had an apparent Km for SAM of 3.3,pM and was inhibited by S-adenosylhomocysteine and S-adenosylethionine.…”
mentioning
confidence: 96%
“…It is insensitive to azide and 2,4-dinitrophenol which strongly inhibit the glucose-dependent accumulation of Sadenosyl-L-methionine in spheroplasts. 4. The transport of S-adenosyl-L-methionine into vacuoles ic optimal at pH 7.4 and is insensitive to nystatin while the uptake of S-adenosyl-L-methionine into spheroplasts is optimal at pH 5.0 and is strongly sensitive to nystatin.…”
mentioning
confidence: 99%
“…The convincing demonstrations by Svihla and co-workers (26)(27)(28) that the ultraviolet microscope can be of considerable use in locating and following the fate of ultraviolet-absorbing substances in living cells provided impetus for the present study. The ability to measure ribonucleoprotein in the chromatoid bodies of living cells has enabled us to draw a much more precise picture of the changes in the concentration of RNA in the cells than has hitherto been possible.…”
Section: Introductionmentioning
confidence: 80%